«EFFECTIVE WAYS OF TEACHING GRAMMAR THROUGH COMMUNICATIVE ACTIVITIES» (Лучшие интеллектуальные исследования, 2025)
Abstract: This article analyses raise the awareness of methods and techniques of teaching communicative grammar effectively, to find effective ways of teaching grammar using communicative games, which can be useful for taking students to new levels, to describe new effective communicative methods of teaching English  grammar not isolated but in context.